What predicts word reading in Arabic? - Hassanein, Elsayed E. A.; Johnson, Evelyn S.; Ibrahim, Sayed; Alshaboul, Yousef (Frontiers in Psychology, 2023)
Efficient and accurate word reading ability is critical for later reading success. As such, it is important to understand the component skills that underlie strong word reading ability. Although a growing research base points to the importance of phonological awareness, morphological processing and orthographic processing for accurate and fluent word reading in Arabic, there are few studies that examine all three areas at one time to better understand their role in word reading. Additionally, it remains unclear whether the contribution of the various processes might differ across the early years when children are learning to read. 1098 pupils in grades 1-3 participated in this study and took tests for phonological awareness, morphological processing, orthographic processing, and word reading accuracy and fluency. According to the findings of regression analyses, the relative contribution of these underlying processes differed according to the method used to test word reading and the student's grade level. Implications and future directions in research are discussed.